Formulation, Implementation, and Control of Competitive Strategy - Pearce II John A (McGraw Hill/Irwin, 2005)
Contemporary research in strategic management, with an emphasis on conceptual tools and skills created by scholars and practitioners in the field are evident throughout this 12-chapter text-only book. Formulation, Implementation, and Control of Competitive Strategy is the softcover, text-only version of Pearce and Robinson’s STRATEGIC MANAGEMENT. Pearce and Robinson presents a unique pedagogical model created by the authors. Instructors who desire quantitative analysis will like the financial data available here. The new, strong coverage of Business Week material provides a currency and uniqueness to the text.